A Web-Based Change Control Management Toolkit for Lump-Sum Turnkey Contractors: Transformation to Third Generation - Omran, Ahmed (AUC Knowledge Fountain, 2021)
Project deviations and changes are one of the key common particulars encountered in the Construction industry. Project changes can occur in different forms, may impact different pillars of the project, and can be caused due to the existence of various underlying factors. Mismanaging or lack of controlling these changes is one of the key contributing factors leading to project hardships. Contractors incur profit erosion, scope creep, and time slippages mainly by failing to have an effective project change management system enforced within its project execution philosophy. Such adversity is amplified for contractors engaging in lump-sum turnkey “LSTK” projects. Contractors encounter a higher level of financial exposure in LSTK projects whereby most of the impacts resulting from project changes are allocated on their liability, in accordance with the principles set out by the contracts. Despite its importance, few contractors engaging in LSTK projects have effective project change management systems. These systems mostly focus on addressing change events caused by the opposing contractual parties that would give rise to a right for entitlement. LSTK contractors are faced a number of barriers whilst attempting to implement the change management techniques such as the required amount of efforts, time consumption, costly applications, unawareness of team members, and improper circulation of data. Moreover, during implementation, other challenges emerge for LSTK contractors, namely the mobility of team members, redundant working steps, and non-utilization of the closed projects’ change management data for the company’s continuous improvements and lessons learned. Thus, this study aims to tackle this matter by: a) designing detailed workflows and working steps for the LSTK EPC contractor to follow for effective project change management, in accordance with the research guidelines, and b) design and develop a comprehensive web-based application that would facilitate the change management workflow, data archiving, and circulation processes. The working steps, and workflows were designed by architecting process flow diagrams that tackle four different scenarios of change management processes that could be encountered in EPC projects: a) engineering, b) procurement, c) construction, d) project management and controls changes. Subsequently, the conceptual and detailed designs of the web-based model, namely the Web-based Change Control and Management Toolkit “WCCMT”, were formulated by identifying and detailing the model’s forms, lists, reports, and dashboard features. The detailed design included defining the field entries, and data relationships for the input component’s forms and data analysis, metrics, and displaying layouts for the output component’s dashboard, lists and reports. Upon completion of the design phase, the WCCMT was developed using a set of four layers a) Web Browser, b) User Interface, c) Application, and d) Database. The model was subsequently tested using a combination of random data entries, as well as data acquired from previous projects, to assess how the model performs under all possible scenarios both on the project and portfolio levels. Afterwards, twenty experts provided their quantitative assessment of the toolkit’s functionality and capabilities as well as the established workflow for the change management which was adopted by the model. The model was validated by carrying out two steps: a) acquiring an extensive feedback by a construction management expert practitioner, and b) enforcing the toolkit to be used in a running EPC project for a LSTK contractor within the Egyptian market. The verification and validation results have demonstrated that the WCCMT’s functionalities and capabilities are satisfactory and acquired a “very good” rating by the construction practitioners with an overall mean score of 4.3 out of 5. The toolkit has demonstrated its capabilities by significantly shortening the change management cycle time and improving the contractor’s system functionality. It centralizes and analyzes the intensive change management data of the registered projects for continuous improvement of the contractor’s performance, both on the project and portfolio levels.